A redox-active gel electrolyte for fiber-shaped supercapacitor with high area specific capacitance1. Issue 12 (28th March 2015) - Pan, Shaowu; Deng, Jue; Guan, Guozhen; Zhang, Ye; Chen, Peining; Ren, Jing; Peng, Huisheng
<x xml:space="preserve">Abstract</x> A fiber-shaped supercapacitor with a gel electrolyte containing 2-mercaptopyridine shows a high specific capacitance of 507.02 mF cm−2.